Os cristãos, de ontem e de hoje, ante a tentação de se acomodarem ao mundo: uma abordagem a partir de Ap 2-3 - Priori, Marcio Luiz (2011)
This study deals with Christians from the beginning to today in the presence of the temptation to accommodate themselves to the world. It takes as point of support Revelation, chapter 2 and 3. In the first part, the research establishes a parallel between Apocalypse of John and the Jewish apocalyptic and the prophetic movement that preceded the apocalyptic movement in Israel. Although the letters written to the churches of Asia Minor, according to The Rev. 2-3, due to the optimism shown with respect to the present history, they are marked by a symbolic language associated with a crisis, since the context of these churches, at the end of the first century, is marked by conflict with the Roman Empire and Judaism. Thus, in the second part, the research shows that the pressure on the populations dominated by the Roman Empire was very strong, and the temptation to adapt them to the imperial system was too great. The Gnostic movement was in favour of the Empire, whose theories penetrated the churches with the support of leaders and members of their communities. In addressing the then seven Churches of Asia Minor, the author of Revelation 2-3 intended to arouse interest the communities to a "threat" that was not only external but also internal, namely the penetration of the Gnostic heresy, which favored adaptation of Christianity to the environment of the Roman Empire. In the third part, we found that the temptation to adapt to the world is still very present today. It's still very current, so the message contained in the letters addressed to the communities of Asia Minor, whose first purpose awaken Christians of their accommodation and their commitment to the present order. For today Christians, "seduced" by the current culture and so well adapted to society, they no longer perceive the contradictions in them, the appeal is to come back to Jesus Christ and "resume the conduct of old" (cf. Rev. 2,5), which means often put in the "opposite" of history, to witness, within a Christian community, that another world is possible.